Lu-177 labelled peptide treatment for radioiodine refractory differentiated thyroid carcinoma - Elboğa, Umut (BMJ Case Rep, 2016)
Differentiated thyroid carcinoma (DTC) has good prognosis but 5% of the patients already have distant metastasis at the diagnosis. Tumour cells can lose their iodine uptake ability and enter a state of dedifferentiation. Treatment for differentiated thyroid carcinoma that is not suitable for the local surgery and unresponsive to radioactive iodine uptake is not always easy for physicians. We present a case of a 64-year-old man who had total thyroidectomy surgery and central lymph node dissection with diagnosis of multinodular goitre disease. Histopathological evaluation was papillary thyroid cancer with tall cell variant. Treatment using 150 mCi radioiodine was administered to the patient three times but could not effect a cure. We performed Ga-68 labelled DOTATE (synthetic somatostatin analogue peptide). This provided a good outcome. As evident from our case, Lu-177 radionuclide labelled synthetic somatostatin analogue peptides have therapeutic effect on radioiodine refractory DTC, as an alternative treatment modality.